(untitled) (Research, Society and Development, 2022)
The Conjunto Vera Cruz, built in 1981, is one of the main housing projects that drive the development of the west side of the municipality of Goiânia. The city of Goiânia was planned for 50 thousand inhabitants, had its rapid development, with large disordered population growth, in 2020, it reached over 1,500,000 (one million and fifth thousand) inhabitants, which was not planning for the municipal. In order to address this type of situation, the Neighborhood Impact Study – EIV was created. Unfortunately, the EIV is not required for residential developments in the city of Goiânia, this may change with the help of published research in case studies. Therefore, the objective of this study is to demonstrate the relevance of the Neighborhood Impact Study for residential projects, a case study of the Residential Nelson Mandela in the Vera Cruz Complex in Goiânia, Goiás, Brazil. In this way, a questionnaire was applied and the urban infrastructure of the neighborhood was evaluated. The questionnaire was applied from February to March 2022, with 60 residents who have lived in the Vera Cruz neighborhood for more than 10 years.